Identification of a New Biocontrol Gene in Trichoderma atroviride: The Role of an ABC Transporter Membrane Pump in the Interaction with Different Plant-Pathogenic Fungi - Ruocco, Michelina; Lanzuise, Stefania; Vinale, Francesco; Marra, Roberta; Turra, David; Woo, Sheridan Lois; Lorito, Matteo (Molecular plant-microbe interactions, 2009)
Successful biocontrol interactions often require that the beneficial microbes involved are resistant or tolerant to a variety of toxicants, including antibiotics produced by themselves or phytopathogens, plant antimicrobial compounds, and synthetic chemicals or contaminants. The ability of Trichoderma spp., the most widely applied biocontrol fungi, to withstand different chemical stresses, including those associated with mycoparasitism, is well known. In this work, we identified an ATP-binding cassette transporter cell membrane pump as an important component of the above indicated resistance mechanisms that appears to be supported by an extensive and powerful cell detoxification system. The encoding gene, named Taabc2, was cloned from a strain of Trichoderma atroviride and characterized. Its expression was found to be upregulated in the presence of pathogen-secreted metabolites, specific mycotoxins and some fungicides, and in conditions that stimulate the production in Trichoderma spp. of antagonism-related factors (toxins and enzymes). The key role of this gene in antagonism and biocontrol was demonstrated by the characterization of the obtained deletion mutants. They suffered an increased susceptibility to inhibitory compounds either secreted by pathogenic fungi or possibly produced by the biocontrol microbe itself and lost, partially or entirely, the ability to protect tomato plants from Pythium ultimum and Rhizoctonia solani attack.